2014
DOI: 10.5902/1980509814573
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento inicial e qualidade de mudas de <i>Pterogyne nitens</i> Tull. conduzidas sob diferentes níveis de restrição luminosa artificial

Abstract: RESUMOObjetivou-se com este estudo avaliar o comportamento de plantas de Pterogyne nitens Tull. sob diferentes níveis de restrição luminosa durante seu desenvolvimento inicial. O estudo foi conduzido no período de março a junho de 2008, no campo agropecuário da Universidade Estadual do Sudoeste da Bahia -UESB, em Vitória da Conquista, BA. Sete experimentos foram definidos por níveis de 20%, 30%, 40%, 50%, 60% e 70% de restrição luminosa e plantas mantidas a pleno sol. Cada um dos experimentos foi organizado em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
2
5
0
5
Order By: Relevance
“…According to César et al (2014), a greater number of leaves in intermediate shades close to 47% observed in the Pterogyne nitens species can be attributed to optimizing photosynthesis and microclimatic conditions, with a reflection on greater carbohydrate accumulation and accelerated leaf emission. Gatti et al (2011) verified that the annual production of Euterpe edulis leaves increased with increasing irradiance, being higher in the treatments corresponding to 65%, lower in the treatment with 10% light, and intermediate in treatments with 30% and 40% of the maximum light.…”
Section: Resultsmentioning
confidence: 99%
“…According to César et al (2014), a greater number of leaves in intermediate shades close to 47% observed in the Pterogyne nitens species can be attributed to optimizing photosynthesis and microclimatic conditions, with a reflection on greater carbohydrate accumulation and accelerated leaf emission. Gatti et al (2011) verified that the annual production of Euterpe edulis leaves increased with increasing irradiance, being higher in the treatments corresponding to 65%, lower in the treatment with 10% light, and intermediate in treatments with 30% and 40% of the maximum light.…”
Section: Resultsmentioning
confidence: 99%
“…Ainda segundo esses autores, é grande a diversidade de respostas das plantas à luminosidade, principalmente no que se refere ao crescimento e desenvolvimento vegetativo da parte aérea. Diante da importância desse fator ambiental, vários autores estudaram a influência do sombreamento na produção de mudas de diversas espécies florestais (Câmara & Endres, 2008;Aguiar et al, 2011;Lenhard et al, 2013;Lopes et al, 2013;Pacheco et al, 2013;César et al, 2014;Santos et al, 2014). Para o nim indiano, porém, até o presente não existe informação disponível na literatura, o que torna esse tipo de estudo de grande relevância para o aprimoramento das técnicas empregadas na produção de mudas dessa espécie.…”
Section: Introductionunclassified
“…Dickson quality index is an appropriate parameter to measure the quality of seedlings, because it defines the strength and balance of biomass distribution in the change (Freitas et al, 2018;Gordin et al, 2016;Jeromine et al, 2019)the higher the value, the better the quality changes (César et al, 2014) Ostiole openings and stomatal indices were greater at 100% WRC, indicating that the plants could better absorb atmospheric CO 2 and would have higher photosynthetic rates under these conditions. The closing of the stomata under water-stress compromises CO 2 acquisition and reduces biomass production and plant productivity -yielding smaller plants with reduced dry weight accumulations, as reported by Rosa et al (2017) for Copaifera langsdorffii Desf., as well as in the study presented here.…”
Section: Discussionmentioning
confidence: 99%